Analysis of Petroleum Products Spill Potential Impact (Gasoline and Diesel Fuels) on Soil Fertility Quality Around Pertamina Rewulu-Cilacap Pipeline Bantul-Yogyakarta - Muthohharoh, Thaifah; Latumahina, Linda Johana; Suyanta, Suyanta; Suherman, Suherman (Universitas Jenderal Soedirman, 2023)
This research focused on analyzing the potential impact of petroleum products spill (gasoline and diesel fuels) on soil fertility quality around PERTAMINA Rewulu-Cilacap Pipeline Bantul, Yogyakarta. The objectives of this study were to analyze the change of soil fertility parameters that are contaminated by gasoline and diesel fuel oils, compared to uncontaminated soil as control. Soil samples were collected from Pertamina Rewulu-Cilacap around the pipeline. Some physico-chemical properties that reflect soil fertility were determined using standard physico-chemical methods and Total Petroleum Hydrocarbon (TPH) using Gas Chromatography. Soil samples were divided into three points (I, II, and III) based on taken places. The study started with analysis of physical and chemical properties of the soil, then petroleum products (gasoline and diesel) were added to the soil samples. The contaminated soil and control then analyzed for identify the fertility quality and TPH content. The results showed that petroleum product contamination increases N, P, and reduces K concentrations in the soil. The sample in point III had the highest values of TPH concentration without any additional petroleum products. After addition of a dose of 13% gasoline, the concentration of TPH in point I, II, and III increased by 0.036%, 0.08% and 0.008%. With the addition of 15% diesel in the sample, the TPH concentration of point I, II, and III increased by 0.892 %, 1.198%, and 0.91%.